Short-Term Inhibition of NOX2 Prevents the Development of Aβ-Induced Pathology in Mice - Kristina A. Mukhina; Olga I. Kechko; Alexander A. Osypov; Irina Yu. Petrushanko; Alexander A. Makarov; Vladimir A. Mitkevich; Irina Yu. Popova (Antioxidants)
Alzheimer’s disease (AD) is the most common neurodegenerative disorder, characterized by the formation of neurotoxic beta-amyloid (Aβ) oligomers in the central nervous system. One of the earliest pathological effects of Aβ is the induction of oxidative stress in brain tissue, mediated by NADPH oxidase 2 (NOX2). This study aimed to determine whether short-term inhibition of NOX2 could disrupt the pathological cascade and prevent the development of Aβ-induced pathology. We demonstrated that suppressing NOX2 activity by GSK2795039 during the first three days after intracerebral Aβ administration prevented the development of the pathological process in mice. Two weeks after the induction of Aβ pathology, animals treated with GSK2795039 showed no neuropsychiatric-like behavioral changes, which correlated with the absence of chronic oxidative damage in brain tissue. Moreover, GSK2795039 prevented microglial activation and reduced microglia-associated neuroinflammation. These findings indicate that short-term NOX2 inhibition effectively suppresses the development of Aβ-induced pathology, suggesting that NOX2 is a potential target for treatment and prevention of AD pathology.